Pengembangan Aplikasi Bank Sampah Berbasis Web Menggunakan PHP dan MySQL - Saryani Saryani; Aliefia Nur Qurratu'AIn; Bunga Reva; Muhamad Hilman Nurlintang; Restu Nugroho; Siti Seli Agustini (Universitas Tangerang Raya, 2025)
Waste banks are a form of waste management thataims to reduce environmental and household waste. This studyaims to design a waste bank system that can assist in the management ofwaste collection and the sale of waste. The method used in this research is a qualitative method and observation fordata collection. Thus, waste banks not only play a role inreducing waste but also encourage the community to be more concernedabout the environment. This program helps residents understand the types ofwaste and how to separate waste based on category. Waste banks can be an alternative solution in managing waste. The existence of waste banks makesthe community more concerned about sorting waste that can be recycled andhas economic value, thereby increasing community incomeand creativity in dealing with waste that can be recycled orreused. The result of creating this website is to prevent the accumulation ofwaste and minimize non-biodegradable waste.